2009
DOI: 10.1097/mpg.0b013e3181a0d269
|View full text |Cite
|
Sign up to set email alerts
|

Use and Safety of Rifaximin in Children With Inflammatory Bowel Disease

Abstract: Rifaximin was well-tolerated and showed favorable results. Larger doses of rifaximin were statistically better for abdominal pain. Further studies are needed to evaluate efficacy and optimal dosing of rifaximin in this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(16 citation statements)
references
References 15 publications
0
15
0
1
Order By: Relevance
“…In our study, the microbial communities are altered before the induction of disease, thereby allowing us to ascertain the effects of community changes on disease development. There is also evidence that the microbial community is important in persistence of bowel inflammation, indicated by antibiotic studies showing amelioration of inflammation after treatment [50,51]. Apart from this, we have little insight into the role of the microbiota in IBD.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, the microbial communities are altered before the induction of disease, thereby allowing us to ascertain the effects of community changes on disease development. There is also evidence that the microbial community is important in persistence of bowel inflammation, indicated by antibiotic studies showing amelioration of inflammation after treatment [50,51]. Apart from this, we have little insight into the role of the microbiota in IBD.…”
Section: Discussionmentioning
confidence: 99%
“…Reduced SCD-1 results in lower levels of unsaturated lysophosphatidylcholine in plasma, which is among the most important anti-inflammatory unsaturated fatty acids 41 . Clinically, rifaximin appears to have more efficacy in the therapy of CD than do traditional medications used to treat IBD such as metronidazole and/or ciprofloxacin 42–43 , due in part to its well-tolerated and efficient effects in adult CD patients 44 as well as for pediatric IBD 45 . Several clinical trials demonstrated that rifaximin decreased intestinal permeability in adult/pediatric patients with gastrointestinal diseases, such as small intestine bacterial overgrowth 46 or tropical enteropathy 47 .…”
Section: Role Of Pxr In the Pathogenesis Of Ibdmentioning
confidence: 99%
“…Other studies revealed that two-thirds of adult patients with Crohn's disease entered remission after rifaximin therapy (Shafran and Burgunder, 2010). A retrospective review revealed a well tolerated and favorable role for rifaximin in pediatric IBD (Muniyappa et al, 2009;Trehan et al, 2009). However, the role of rifaximin in irritable bowel syndrome and IBD therapy and its mechanisms of action are not understood.…”
Section: Introductionmentioning
confidence: 99%